Determinants of Consumer Attitudes Towards Social Media Advertising: Evidence from the Turkish Airline Industry - Mahmut Bakir; Huseyin Korkmaz; Selin Sak Fatma; Ozlem Atalik (Studies in Business and Economics, 2022)
As the prevalence of social media increases, it is considered as an important promotion outlet for the airline industry. The main motivation behind this paper is to identify the determinants of attitude towards social media advertising in the context of the Turkish airline industry. The model of advertising value lies in the theoretical foundation of this paper. Employing a convenience sampling, a questionnaire was completed by 123 users of social media in Turkey. The Partial Least Squares Structural Equation modeling (PLS-SEM) approach was employed to test the hypothesized relationships. Results revealed that informativeness, entertainment, and credibility are positively associated with advertising value, thus affecting attitude towards social media advertising. On the other hand, irritation has no significant relation with advertising value.